Boosting the epoxidation of long-chain linear α-olefins via bimetallic CoIr composite. (15th October 2022) - Zhou, Ziyu; Wang, Fan; Yan, Tao; Wan, Hongliu; Yao, Ru; Zhang, Kun; Liu, Yangping; Wang, Shuyuan; Xu, Dan; Hou, Huaming; He, Peng; Li, Yongwang; et al.
Graphical abstract: We report a novel approach to prepare a bimetallic CoIr composite catalyst and it exhibits an unrivaled space-time yield in production of 1, 2-epoxydecane, approximately 6 times to that state-of-the-art Co-based precedent. This strategy also shows excellent compatibility to extended substrate scope and promising future in valorization of Fischer-Tropsch synthesis crude. Highlights: The bimetallic CoIr composite catalyst was prepared via pyrolysis of molecularly defined "Co-Ir" pair complex pre-catalyst. The CoIr composite catalyst exhibited an unrivaled space-time yield, approximately 6 times to that state-of-the-art Co-based precedent. The atomically well-dispersed electron-rich Co site could promote elementary cleavage of the "O-O" bond in the key ROO intermediate. The CoIr composite catalyst showed excellent compatibility to extended substrate scope and promising future in valorization of Fischer-Tropsch synthesis crude. Abstract: Fischer-Tropsch Synthesis (FTS) offers a premier route for mass production of industrially valuable long-chain linear α-olefins (LAOs), which cannot be directly separated for further use. Epoxidation of LAOs in FTS mixture allows for easier separation of them, however, the reaction by itself remains a substantial challenge. Herein, we prepared a Co-Ir composite via pyrolysis of molecularly defined "Co-Ir" pair complex and it exhibits an unrivaled space-time yield of 17.5 molepo ·molCo −1 ·h −1 in production of 1, 2-epoxydecane, approximately 6 times to that state-of-the-art Co-based precedent. Varieties of experimental and theoretical characterizations reveal that atomically well-dispersed electron-rich Co is key in the promotion of ROO dissociation into RO. This strategy further succeeds in epoxidation of mixture containing 1-decene and n -decane, evident for its wide-range compatibility. This work greatly advances valorization of long-chain LAOs and separation of their value-added derivatives.